Clinical features of H1N1 2009 infection in critically ill immunocompromised patients - Camous, Laurent (BioMed Central, 2010)
Seasonal influenza virus has been described as an emerging and severe pathogen in immunocompromised hosts. Since the beginning of the 2009 influenza A novel H1N1 pandemic, several series have described the clinical course of the disease in various populations. We report the clinical course of H1N1 2009 infection in 10 immunocompromised patients. Half of the patients received long-term steroid therapy. Disease was characterized by a clinical picture similar to that of non-immunocompromised patients but with prolonged course and higher mortality.